Nail psoriasis treated with pulse dye laser - Ahmed Al Mutairi; Muhammad Elkashlan (Wolters Kluwer Medknow Publications, 2013)
Pulse dye laser has proved effective for plaque-type psoriasis, but it has not been evaluated in nail psoriasis. We are reporting treatment of 10 psoriatic nails in one patient with pulse dye laser.